Korelasi antara Interaksi Sosial Terhadap Hasil Belajar Afektif Siswa Sekolah Dasar - Dini Sari; Mutrofin Mutrofin; Chumi Fitriyah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
Social interaction is the relationship between one individual and another individual, one individual can influence other individuals so that there is reciprocity. The better the students' social interactions, the better their learning outcomes will be. Learning outcomes examined in this study are affective learning outcomes. This study aims to reveal whether the better social interaction, the better the affective learning outcomes of fifth-grade students in SDN throughout Kaliwates Jember District. The population of this research is the fifth-grade students of SDN in Kaliwates Jember District. This study is a correlation study with a population of 182 and a sample of 25 students. The main methods of collecting data are questionnaire and observation. To test the research hypothesis using the product-moment correlation formula with the help of SPSS 20 at a significance level of 5%. The results of the research analysis obtained the value of r_count r_tabel (0.748 0.266) and the coefficient of determination 56%. This shows that social interaction has a contribution of 56% to affective learning outcomes the remaining 44% is influenced by other factors. It can be concluded that the better social interaction, the better the affective learning outcomes of fifth-grade students of SDN in Kaliwates Jember District.Keywords: Social interaction, affective learning outcomes, elementary school student